SSCP typing of alpha-lactalbumin and beta-lactoglobulin gene and its association with milk production and constituent traits in Indian riverine buffalo - Vohra, Vikas; Dayal, Shankar; Bhattacharya, Tarun Kumar (The Indian Journal of Animal Sciences, 2012)
A study was conducted to explore genetic polymorphism in alpha-lactalbumin and beta-lactoglobulin gene and to elucidate the effect of polymorphism on milk production and constituent traits in Indian riverine buffaloes namely, Murrah, Bhadawari, Mehsana and Surti. Single strand conformation polymorphism (SSCP) was conducted on exon II of alpha-lactalbumin and exon I of beta-lactoglobulin gene. The study on alpha-lactalbumin gene revealed the presence of a number of genotypes namely, AB, AC, BB, BC, BD and BE in Mehsana; AC, BB, BC, BD, BE and CC in Surti; AC, BB, BC, BE and CC in Bhadawari and BC, BE, CC and CD in Murrah buffalo. In beta-lactoglobulin gene, genotypes like AA, BB, CC, AB and AC were observed in Murrah buffalo; AA, BB, AB and AC in Mehsana; AA, BB, CC, AB and AC in Surti and BB, CC, AB and AC in Bhadawari buffalo. All the alleles were sequenced and found to be differed at different locations. The alpha-lactalbumin genotypes had significant effect (P<0.05) on fat%, daily fat yield, total fat yield, SNF%, daily solid not fat and total solid not fat yield in Murrah buffalo; whereas, in Surti breed total milk yield, daily solid yield, total solid, daily solid not fat, total solid not fat yield, daily and total protein yield were significantly associated with the genotypes. The beta-lactoglobulin genotypes showed significant effect (P<0.05) on daily milk yield in Murrah, Bhadawari and Mehsana buffalo. In all the breeds, BB genotypes produced highest daily milk yield. In Murrah, Bhadawari and Mehsana breed, genotypes AA, CC and AC were associated with lowest production.